Literasi Keuangan dan Pertanian Kakao Berkelanjutan - Ayu Kartini Parawansa; Aslam, Annisa Paramaswary; Kalla, Rastina (Lembaga Pengembangan Kinerja Dosen, 2025)
Cocoa farming is one of the plantation subsectors that plays a strategic role in Indonesia’s economy, as it contributes to increasing farmers’ income, national exports, and the development of the chocolate processing industry. Indonesia is recognized as one of the world’s largest cocoa producers, with major production areas located in Sulawesi, particularly South Sulawesi, Central Sulawesi, and Southeast Sulawesi. However, the sustainability of cocoa farming still faces various challenges, such as low crop productivity, the use of low-quality seedlings, suboptimal cultivation techniques, and the presence of pests and plant diseases. In addition, limited access to capital and the low level of farmers’ financial management skills also affect the sustainability of cocoa farming. Many farmers do not yet have proper farm financial record-keeping systems, making it difficult to manage production costs, cash flow, and farm capital planning. In this context, financial literacy becomes an important factor that can help farmers manage their farming activities more effectively and sustainably. This study aims to analyze the effect of financial literacy on the sustainability of cocoa farming and farmers’ welfare. The research employs a quantitative approach using a survey method involving 120 cocoa farmers in Sidenreng Rappang Regency (Sidrap), South Sulawesi. Data were collected through questionnaires and interviews and then analyzed using multiple linear regression analysis. The results indicate that financial literacy has a positive and significant effect on farm financial management and the sustainability of agricultural businesses. Farmers with higher levels of financial literacy tend to manage farm capital more effectively, maintain proper financial records, and improve farm productivity. Therefore, improving financial literacy can become